Аналіз та оцінка впливу шкідливих викидів ТЕС України на навколишнє середовище - Коваленко, Тетяна; Коваленко, Павло (Видавництво Львівської політехніки, 2013)
The development of science and technology continually affects the growth of human impact on the environment. Especially in our time, the problem of pollution of the atmosphere, lithosphere and hydrosphere and their negative impact on the biosphere, human life and health becomes more and more relevance in the world. Therefore, the analysis of current research and publications concerning the effects of emission of thermal power plants in Ukraine on the environment have been done in this work. The reasons that lead to the pollution of the biosphere were generalized and the ways to overcome this environmental problem were given. The main conclusions of the work were made according to the scientific research.
Keywords: теплові електричні станції; паливо; шкідливі викиди; забруднення біосфери; навколишнє середовище; екологічна проблема